2002
DOI: 10.1161/01.cir.0000030181.63741.56
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–Induced Cardiac Hypertrophy and Hypertension Are Attenuated by Epidermal Growth Factor Receptor Antisense

Abstract: Ang II requires EGFR to mediate ERK activation in VSMCs and the heart. EGFR plays a critical role in the LVH induced by Ang II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
1
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 20 publications
2
117
1
5
Order By: Relevance
“…30,33 Ald also mediated its effects via the EGFR. Ald enhanced EGF signaling, resulting in potentiated ERK 1/2 phosphorylation and Ca 2ϩ homeostasis in MDCK cells.…”
Section: Mazak Et Al Angiotensin II and Aldosterone 2797mentioning
confidence: 97%
“…30,33 Ald also mediated its effects via the EGFR. Ald enhanced EGF signaling, resulting in potentiated ERK 1/2 phosphorylation and Ca 2ϩ homeostasis in MDCK cells.…”
Section: Mazak Et Al Angiotensin II and Aldosterone 2797mentioning
confidence: 97%
“…Until now, the popular technology to reduce angiotensin receptors has been the use of antisense oligonucleotides. [13][14][15][16][17][18] RNAi technology not only is highly selective for the subtypes of AT 1a R and AT 1b R but also is more effective than antisense oligonucleotides. For example, a previous study 19 demonstrated a reduction of AT 1 R by 57% to 73% with 1 mol/L concentration of AT 1 R-specific antisense oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that EGFR transactivation plays an important role in cardiovascular remodeling (8,20,(30)(31)(32). It has been reported that activation of ADAM12 (8) or ADAM17 (22) could induce the release of HB-EGF and subsequent EGFR phosphorylation, which may eventually lead to cardiomyocyte hypertrophy, while inhibition of ADAM12 or administration of an HB-EGF neutralizing antibody blocked GPCR agonist-stimulated myocyte hypertrophy (8).…”
Section: Fig 5 Atorvastatin Inhibited the Egfr-erk Signaling Pathwamentioning
confidence: 99%